The Impact of Sudden Public Health Events on the Insurance Companies' Investment Returns: Based on the Investors' Sentiment Perspective - Shang, Yunfeng; Qian, Fangbin; Gao, Nan; Yang, Qin; Guo, Yiting; Sun, Yunpeng (Frontiers in Public Health, 2022)
This study analyzes the conflicting effects of investors’ sentiment caused by public health emergencies and uses event analysis methods and linear regressions to examine the impact of such emergencies on the stock prices of insurance companies. The study shows that public health emergencies have a positive and significant impact on insurance companies’ portfolios through investors’ sentiment, which is persistent. However, the investor fear index triggered by public health emergencies is negatively associated with insurance stock portfolio returns. Meanwhile, insurers with smaller market capitalization are more strongly influenced by investors’ sentiment than those with larger market capitalization.